Effects of exposition to polluted environments on blood cells of the fish Prochilodus lineatus - Pereira, Bruno Fiorelini [UNESP]; Da Silva Alves, Rebeca Mamede [UNESP]; Pitol, Dimitrius Leonardo; Senhorini, Jose Augusto; Gimenes de Alcantara Rocha, Rita de Cassia; Caetano, Flávio Henrique [UNESP] (Wiley-Blackwell, 2012)
In this study, we investigated the effects of contaminated water on the blood parameters of the fish Prochilodus lineatus exposed during 7 and 20 days. Blood was collected with heparinized syringes, and blood smears were prepared and stained with Leishman stain. Slides were examined and photographed using a Leica light microscope. Total white blood cell counts and differential counts of thrombocytes and leukocytes were obtained for statistical analysis. The group exposed to water samples from Lago Azul exhibited an increase in the number of leukocytes and in the total number of white blood cells, suggesting that the chemical contaminants in this environment were acting similarly to antigens in this fish species, causing the proliferation of defense cells. In the group exposed to detergent during 20 days, the number of thrombocytes decreased. These results suggest that the variations in the number of leukocytes were indicators of environmental pollution and that biodegradable detergents may, after a certain time of exposure, affect vital functions in fish, such as coagulation and prevention of infections, which directly involves thrombocytes. Microsc. Res. Tech., 2012. (c) 2011 Wiley Periodicals, Inc.
Keywords: blood; thrombocytes; leukocytes; fish; polluted environments